Central Continental Boreal Summer "Warming Holes" Modulated by Atlantic Multidecadal Oscillation Via Low‐Level Jets. Issue 1 (4th January 2022) - Pan, Zaitao; Kumar, Sanjiv; Zhang, Yuanjie; Shi, Chunhua
Abstract: Despite the accelerated global warming, the central‐eastern U.S. experienced summer daytime cooling during the 20 th century. A number of studies have attributed various factors responsible for this abnormal regional cooling, termed the "warming hole (WH)". This study demonstrates that another WH also existed in the south‐central China that shares similar temporal trend and geographical location to the U.S. WH, including the cooling reversal around 1995. Generalizing the two WHs unravels that they both occurred (a) to the east of major mountain ranges, (b) in heavily cultivated agricultural regions, and (c) near the terminus of the low‐level jets. This study further finds that the WH patterns are the leading mode of surface maximum temperature variability in summer of their respective regions. The WH cooling was consistent with reduction in cloud‐forced solar radiation supported by moisture convergence through weakening of low‐level southerly flow downstream of China WH and strengthening of the southerly flow upstream of U.S. WH. The long‐term trends of WH temperature are highly correlated to the Atlantic Multidecadal Oscillation (AMO) and WH cooling turned into warming around 1995 when the AMO shifted to the positive phase, which combined with overall regional warming, may explain why the summer WH phenomenon has been in diminution for past two decades or so. Given the AMO's association with global climate trend, the WH phenomenon could also be viewed as a local thermal response to the global warming via AMO modulation of regional dynamic and moisture circulation. Plain Language Summary: Despite the accelerated global warming, the central‐eastern U.S. experienced summer daytime cooling during the 20 th century. This abnormal regional cooling was termed the "warming hole (WH)". This study demonstrates that another WH also existed in the south‐central China that shares similar temporal trend and geographical location to the U.S. WH, including the cooling reversal around 1995. Generalizing the two WHs unravels that they both occurred (a) to the east of major mountain ranges, (b) in heavily cultivated agricultural regions, and (c) near the terminus of the low‐level jets. The WH cooling was consistent with reduction in cloud‐forced solar radiation supported by moisture convergence through low‐level southerly flow that is in turn modulated by Atlantic Multidecadal Oscillation. Key Points: Defying global warming, south‐central China and central eastern U.S. has experienced cooling in 2nd half of 20th century The cooling regions are located to the east of major mountain ranges, in heavy agricultural areas, and downstream of low‐level jets The cooling is highly correlated with Atlantic Multidecadal Oscillation that modulates low‐level jet and thus clouds/radiation/precipitation